Association of Organochlorine Pesticides With Genetic Markers of Endoplasmic Reticulum Stress in Type 2 Diabetes Mellitus: A Case–Control Study Among the North-Indian Population - Tawar, Neha; Banerjee, Basu Dev; Madhu, Sri Venkata; Agrawal, Vivek; Gupta, Sanjay (Frontiers in Endocrinology, 2022)
Background: Organochlorine pesticides (OCPs) have been long linked to type 2 diabetes mellitus (T2DM), however, this relation at the molecular level has not been explored yet. Endoplasmic reticulum (ER) stress and pro-inflammatory pathways are considered vital ones in the pathogenesis of T2DM. We aimed to investigate the existence of any association between OCPs, ER stress and pro-inflammatory pathways in subjects with known T2DM. Methods: Seventy subjects each with T2DM and normal glucose tolerance were recruited from the Surgery department. Their visceral adipose tissue was collected intraoperatively. OCPs concentration, ER stress, and pro-inflammatory markers were analyzed and compared between two study groups. Results: We found 18 OCPs and their metabolites in visceral adipose tissue samples of study participants. The levels of δ-HCH, heptachlor, endrin, and p,p’DDT were significantly higher in T2DM group and were also positively correlated with fasting and postprandial plasma glucose levels (p<0.01). We observed a positive association of δ-HCH (p<0.01), heptachlor (p<0.05), and endrin (p<0.05) with central adiposity and ER stress markers. However, we failed to establish the correlation of OCPs with any of the pro-inflammatory markers. Conclusion: The existence and simultaneous complex correlation of OCPs with ER stress may explain their role in the pathogenesis of T2DM, revealing the persistence of gene-environment interaction in the etiology of T2DM.